2018
DOI: 10.31237/osf.io/3nfgh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When and why is “extraversion” associated with social popularity?

Abstract: Examinations of the relationship between individuals’ personal characteristics and the social positions that individuals receive in everyday peer networks have often found an association between extraversion and popularity. This thesis assesses the conditions (when) and mechanisms (why) of this association.Four research questions focus on when the link between extraversion and popularity is present. The study examines whether extraversion is already associated with popularity among seven- to eight-year-olds (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 216 publications
(403 reference statements)
1
6
0
Order By: Relevance
“…Indeed, we find this even in the context of the COVID-19 pandemic (Shokrkon and Nicoladis, 2021) and our own results show that extraversion is negatively correlated with loneliness, positively associated with social support, and positively correlated with having more close friends, spending more time with friends, participant's satisfaction with the number of friends they had, the time they spend with their friends over the previous week, and how much time they would like to spend with friends on a weekly basis. Although people with higher extraversion may very well have experienced a greater change in their social lives, relative to people with higher introversion, as a result of pandemic restrictions (Folk et al, 2020), our findings nevertheless demonstrate that higher extraversion is correlated with stronger social connectedness, more positive interpretation of their social situation, and greater perceived social support, which supports much of the extant work on this topic (Ilmarinen, 2018;Pollet et al, 2011;Roberts et al, 2008;Wang et al, 2021).…”
Section: Primary Findingssupporting
confidence: 79%
“…Indeed, we find this even in the context of the COVID-19 pandemic (Shokrkon and Nicoladis, 2021) and our own results show that extraversion is negatively correlated with loneliness, positively associated with social support, and positively correlated with having more close friends, spending more time with friends, participant's satisfaction with the number of friends they had, the time they spend with their friends over the previous week, and how much time they would like to spend with friends on a weekly basis. Although people with higher extraversion may very well have experienced a greater change in their social lives, relative to people with higher introversion, as a result of pandemic restrictions (Folk et al, 2020), our findings nevertheless demonstrate that higher extraversion is correlated with stronger social connectedness, more positive interpretation of their social situation, and greater perceived social support, which supports much of the extant work on this topic (Ilmarinen, 2018;Pollet et al, 2011;Roberts et al, 2008;Wang et al, 2021).…”
Section: Primary Findingssupporting
confidence: 79%
“…In accordance with previous research (Carlson & DesJardins, 2015;Ciarrochi & Heaven, 2009), we predicted a positive association between self-reported extraversion and other-rated popularity (H1). In addition, building on previous findings on cues of dominant behaviour (Back, Schmukle, & Egloff, 2011;Breil et al, 2020;Ilmarinen, 2018), we subsequently expected positive associations of extraversion and dominant behaviours (H2) as well as dominant behaviours F I G U R E 1 Hypothesized mediation model of the current study. Note: In both studies, we expected associations between self-reported extraversion and other-rated popularity (H1), between self-reported extraversion and observer-rated dominant behaviours (H2), and between observer-rated dominant behaviours and other-rated popularity (H3).…”
Section: The Present Studymentioning
confidence: 72%
“…The association between extraversion and popularity has been consistently found in both laboratory (Carlson & DesJardins, 2015) and real-life settings (Back, Schmukle, & Egloff, 2011;Ciarrochi & Heaven, 2009;van der Linden et al, 2010), as well as across different age groups (e.g., children, adolescents, young adults; Carlson & DesJardins, 2015;Ilmarinen, 2018;Szczygiel & Mikolajczak, 2018;van der Linden et al, 2010). Whereas most of these studies used well-acquainted samples, such as college dormitories (Wortman & Wood, 2011) or school classes (Ciarrochi & Heaven, 2009;Ilmarinen, 2018;Szczygiel & Mikolajczak, 2018;van der Linden et al, 2010), the association between extraversion and popularity was also established in zero acquaintance settings. In two previous studies, university students with higher extraversion were rated as more popular by their fellow students after introducing themselves at their first lecture (Back, Schmukle, & Egloff, 2011) and when interacting in small groups (4-6 people) during free conversation or an ice-breaking game (Carlson & DesJardins, 2015).…”
Section: Backgrou N Dmentioning
confidence: 97%
See 2 more Smart Citations